2021
DOI: 10.3389/fphar.2021.658079
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Effective Treatment for Anemic Patients With Chronic Kidney Disease: An Updated Systematic Review and Meta-Analysis on Roxadustat

Abstract: Background: Roxadustat is a new oral drug for anemia in chronic kidney disease (CKD). This study aimed to synthesize the evidence from randomized controlled trial (RCT)-based studies that estimated the efficacy and safety of roxadustat in anemia patients with non-dialysis-dependent (NDD) and dialysis-dependent (DD) CKD.Methods: We searched the PubMed, Web of Science, and Cochrane Central Register of Controlled Trials (CENTRAL) databases for related published studies. Moreover, we manually searched relevant pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
1
9
0
1
Order By: Relevance
“…The previous meta-analysis of RCTs by Tang et al [41] included eight RCTs with a total of 5,379 NDD-CKD patients. They concluded that ROX was associated with increased hemoglobin level weighted mean difference {WMD}: 1.36 g/dL; 95% CI: 0.90, 1.82; p < 0.00001, transferrin level (WMD: 0.6 g/L; 95% CI: 0.24, 0.95; p < 0.0009), and TIBC level (WMD: 59.90 μg/ dL; 95% CI: 38.85, 80.96; <0.00001).…”
Section: Plos Onementioning
confidence: 99%
“…The previous meta-analysis of RCTs by Tang et al [41] included eight RCTs with a total of 5,379 NDD-CKD patients. They concluded that ROX was associated with increased hemoglobin level weighted mean difference {WMD}: 1.36 g/dL; 95% CI: 0.90, 1.82; p < 0.00001, transferrin level (WMD: 0.6 g/L; 95% CI: 0.24, 0.95; p < 0.0009), and TIBC level (WMD: 59.90 μg/ dL; 95% CI: 38.85, 80.96; <0.00001).…”
Section: Plos Onementioning
confidence: 99%
“…Similarly, Kaplan-Meier survival curves from a FDA report (U.S.Food & Drug Frontiers in Pharmacology frontiersin.org Administration, 2021) supported that the OT+28 roxadustat has statistically significantly higher mortality than ESAs, although the causes of death were not adjudicated. It is worth mentioning that some previous studies reported no statistical difference in all-cause mortality between the roxadustat group and the ESAs or placebo group due to shorter follow-up (Barratt et al, 2021b) or earlier publication (Tang et al, 2021). Although both studies found slightly higher all-cause mortality in the roxadustat group.…”
Section: Discussionmentioning
confidence: 81%
“…Third, recent meta-analysis indicated that standard-dose roxadustat therapy could increase serious incidences of treatment-emergent adverse events compared with ESA in non–dialysis-dependent CKD population. 25 , 26 Taken together, more heterogeneous and long-term interventional studies should be performed to observe the effectiveness and safety of different initial-dose regimens and dosing-adjustment strategies for anemia correction.…”
Section: Discussionmentioning
confidence: 99%